To evaluate and compare analgesic effects of wound infiltration with voveron with intravenous injection in cesarean section - Saraf, Smriti; Batra, Mahima; Songir, Sheetal; Kumar Thakur, Krishna; Gaikawad, M.R. (International Journal of Medical Research and Review, 2016)
Objectives: Postoperative pain mostly results from sensitization of afferent fibers at injury sites driving central sensitization. Recently, peripheral processes have gained attention as mechanism of hyperalgesia, and prostaglandins are among highly sensitizing agents. To date, postoperative administration of a one single intravenous dose of voveron has shown inconclusive efficacy. Rather than a single intravenous dose, the current study evaluates the postoperative analgesic effect of local injection of voveron sodium after cesarean delivery. Methodology: In a prospective randomized, controlled study, 60 patients age group between 18-35 years, scheduled for routine and emergency cesarean surgery were distributed into two groups of 30 patients each. Postoperatively, group [B] was given voveron in wound local injection and group [A] received voveron 75 mg conventionally as intravenous injections. Pain intensity score, onset of analgesia, rescue analgesia doses and overall patient satisfaction score were recorded. Results: Mean onset of analgesia was 8.31 ± 1.5 min with group A as against 4.23 ± 1.2 min with group B. Pain Intensity (PPI) score ≤ 1 was observed in 78.21% observations belonging to group A and in 50 % observations of group B. Twenty five patients (71.4%) from group A and 30 patients (85.7%) from group B required rescue analgesia. The patient’s feedback was graded as very good or good by 78.5% of the patients in Group-A and 69% patients in Group-B. Conclusion: Though both drugs are equally safe, Voveron in local wound infusion is faster acting, more potent and efficient analgesic than intravenous. voveron when used for postoperative pain